EFEKTIVITAS MANDI REMPAH DALAM MENURUNKAN TINGKAT KECEMASAN PADA IBU POSTPARTUM DI PMB WULAN MARDIKANINGTYAS KARTASURA - Ayuk Kaswaroh, Diah; Aris Prastyoningsih; Desy Widyastutik (Rena Cipta Mandiri, 2025)
The postpartum period is often accompanied by anxiety that can develop into postpartum depression if left untreated. A spice bath is a non-pharmacological method believed to provide relaxation. This study aimed to determine the effect of a spice bath on postpartum maternal anxiety levels at PMB Wulan Mardikaningtyas Kartasura. This study used a quasi-experimental design with a one-group pretest-posttest approach on 30 postpartum mothers. Data analysis used the Wilcoxon test. The average anxiety score decreased from 27.77 to 17.90 after the spice bath (p-value = 0.000), indicating a significant difference between anxiety levels before and after the intervention. In conclusion, a spice bath is effective in reducing postpartum maternal anxiety levels and can be used as a complementary therapy during the postpartum period.